Asynchronous delivery in a twin pregnancy. First case report in Peru - Hernández Martínez, Adela María (2022)
Asynchronous delivery (AD) or delayed delivery is a rare presentation of multiple gestation. This occurs when one fetus is born vaginally and the remaining fetus or fetuses are kept in utero and are born with a difference of days or weeks. The is the first report in Peru of a pregnant woman whose first delivery was at 20.1 weeks and the second at 24.4 weeks, and the management and perinatal results of the case are detailed. The evidence suggests that an AC improves survival and reduces morbidity and mortality of the second fetus. It is essential to continue research on this topic to describe its real prevalence, identify ideal candidates, standardize obstetric management and thus optimize maternal and fetal outcomes.